Improvements in Immune Function and Activation with 48-Week Darunavir/Ritonavir-Based Therapy: GRACE Substudy. (12th December 2013) - Tsoukas, Christos; Gilbert, Louise; Lewis, Trevor; Hatzakis, George; Falcon, Ron; Mrus, Joseph
Abstract : Objective . During the course of HIV infection, progressive immune deficiency occurs. The aim of this prospective substudy was to evaluate the recovery of functional immunity in a subset of patients from the GRACE (Gender, Race, And Clinical Experience) study treated with a DRV/r-based regimen. Methods . The recovery of functional immunity with a darunavir/ritonavir-based regimen was assessed in a subset of treatment-experienced, HIV-1 infected patients from the GRACE study. Results . 19/32 patients (59%) enrolled in the substudy were virologically suppressed (<50 copies/mL). In these patients, median (range) CD4+ cell count increased from 222 (2, 398) cells/mm 3 at baseline to 398 (119, 812) cells/mm 3 at Week 48. CD8+% decreased significantly from baseline to Week 48 (P = .03 ). Proliferation of CD4+ lymphocytes in response to CD3+/CD28+, phytohemagglutinin, and pokeweed was significantly increased (P < .01 ) by Week 12. Proliferation in response to Candida and tetanus was significantly increased by Week 48 (P < .01 andP = .014, resp.). Staphylococcal enterotoxin B-stimulated tumor necrosis factor-alpha and interleukin-2 in CD4+ cells was significantly increased by Week 12 (P = .046 ) and Week 48 (P < .01 ), respectively. Conclusions . Darunavir/ritonavir-based therapy demonstrated improvements in CD4+ cell recovery and association with progressive functional immune recovery over 48 weeks. This trial is registered withNCT00381303 .